فھم معاني المفردات والتراكیب اللغویة لدى تلامیذ المرحلة الابتدائیة - أ.د. كامل محمود نجم م.م.یسرى مھدي حسون (College of Education for Women, 2019)
This study aims at exploring primary school pupils' understanding of the meaning of lexical items and language structures. The study sample consists of 40 second year primary school pupils. The results reveal that the percentage of the pupils'. Understanding of the meaning of lexical items is 72.7% that of language structures "verbal and nominal clauses" is 82.3% and that of language structures "negative, interrogative, vocative, reference and prepositions" is 86.5%. The study also reveals that there is no statistically significant difference between the achievement of male pupils and that of females.